Visual Priming Enhances the Effects of Nonspatial Cognitive Rehabilitation Training on Spatial Learning After Experimental Traumatic Brain Injury. (October 2015) - Edwards, Clarice M.; Kumar, Krishma; Koesarie, Kathleen; Brough, Elizabeth; Ritter, Anne C.; Brayer, Samuel W.; Thiels, Edda; Skidmore, Elizabeth R.; Wagner, Amy K.
Previous work demonstrates that spatial (explicit) and nonspatial (implicit) elements of place learning in the Morris water maze (MWM) task can be dissociated and examined in the context of experimental traumatic brain injury (TBI). Providing nonspatial cognitive training (CT) after injury can improve place learning compared with untrained controls. In the present study, we hypothesized that brief exposure to extra-maze cues, in conjunction with CT, may further improve MWM performance and extra-maze cue utilization compared with CT alone. Adult male Sprague-Dawley rats (n = 66) received controlled cortical impact (CCI) injury or sham surgery. Beginning day 8 postsurgery, CCI and sham rats received 6 days of no training (NT) or CT with/without brief, noncontextualized exposure to extra-maze cues (BE and CT, respectively). Acquisition (days 14-18), visible platform (VP; day 19), carryover (CO; days 20-26), and periodic probe trials were performed. Platform latencies, peripheral and target zone time allocation, and search strategies were assessed. CCI/BE rats had shorter acquisition trial latencies than CCI/NT ( P < .001) and tended to have shorter latencies than CCI/CT rats ( P < .10). Both BE and CT reduced peripheral zone swimming for CCI rats versus CCI/NT. CCI/BE animals increased spatial swim strategies from day 14 to day 18 relative to CCI/CT and showed similar swim strategy selection to the Sham/NT group. These data suggest that visual priming improves initial place learning in the MWM. These results support the visual priming response as another clinically relevant experimental rehabilitation construct, to use when assessing injury and treatment effects of behavioral and pharmacological therapies on cognition after TBI.